Desain dan Implementasi Program Layanan Jemaat GKJ Gondokusuman Yogyakarta dengan Metode RAD - Yossie Ruben Advindo; Gani Indriyanta; Hendro Setiadi (Fakultas Teknologi Informasi, 2022)
The development of GKJ Gondokusuman which became an open church made church boards and pastors required to give satisfaction to the congregation. With these problems, it is necessary to have an application for the GKJ Gondokusuman congregation data collection service program. Where in the GKJ Gondokusuman congregation data collection service application, the church congregation can independently update their personal data. The development of this application will apply the Rapid Application Development (RAD) method by following the stages starting with requirements planning (planning the terms), followed by a RAD design workshop, and ending with implementation. The GKJ Gondokusuman congregation data collection service application program was successfully built in this study. Each stage of the RAD method in developing the GKJ Gondokusuman service application runs smoothly and well, as evidenced by the black box test results that have been carried out by the GKJ Gondokusuman service application, which can be used to update the personal data of the congregation members.